Influence of ultrasound on the growth striations in GaₓIn₁₋ₓSb single crystals - Zolkina, L.V.; Kozhemyakin, G.N. (Functional Materials, 2005)
The results of investigation experiments of the growth striations in GaₓIn₁₋ₓSb single crystals with х=0.03 grown by Czochralski method with ultrasound field at a frequency of
1.44 MHz have been presented. It was noted that ultrasound eliminate the growth striations generated by the convection in the melt in the central part of the crystals and at the crystals periphery. The experimental results have been confirmed by the modeling experiments of the convection in the liquid phase in the conditions similar to growth conditions of Ga₀.₀₃ln₀.₉₇Sb single crystals. Наведено результати експериментiв дослiдження шарової неоднорiдностi у монокристалах твердих розчинiв GaₓIn₁₋ₓSb з вмiстом галiю х = 0,03, вирощених методом Чохральського при впливi ультразвукового поля з частотою до 1,44 МГЦ. Встановлено, що ультразвук усуває в центральної частинi та на периферiї кристалiв шари, що мають конвективну природу. Результати вказаних експериментiв вирощування пiдтверджено експериментами моделювання конвекцiї у рiдкiй фазi в умовах, близьких до умов росту монокристалiв Ga₀.₀₃ln₀.₉₇Sb. Приведены результаты экспериментов по исследованию слоистой неоднородности в монокристаллах твердого раствора GaₓIn₁₋ₓSb с содержанием Галлия х = 0.03, выращенных методом Чохральского при воздействии ультразвукового поля с частотой до 1,44 МГЦ. Установлено, что ультразвук устраняет в центральной части и на периферии кристаллов слои, имеющие конвективную природу. Результаты данных экспериментов роста были подтверждены экспериментами моделирования конвекции в жидкой фазе в условиях, близких к условиям роста монокристаллов Ga₀.₀₃ln₀.₉₇Sb.